Study of heterosis in single-cross hybrids of sunflower - Mohamed, Mohamed Y; Mohamed E, Ibrahim N. Elzein; Ibrahim, Abu Elhassan Ibrahim (Gezira Journal of Agricultural Science; Vol 12 No 2 (2014), 2014)
This study was conducted to estimate the genetic variability and heterosis of 40 F 1 hybrids of sunflower for seed yield and its components over two seasons (summer and winter) in 2007 at Sennar Research Station Farm in central Sudan. The plant material consisted of 14 sunflower parents            (4 females and 10 males) and their 40 F 1 -hybrids. The experiment was arranged in a randomized complete block design with three replicates. The traits measured were days to 50% flowering, plant height, head diameter, number of seeds per head, one thousand seed weight and seed yield.  Hybrids showed high genetic variability for all traits studied than their parents which suggested some degree of hybrid vigor. The direction and magnitude of heterosis varied from cross to cross. Over two seasons, the average mid-parent heterosis in preferred direction and magnitude depicted that the hybrid SA2 x SR41 followed by SA3 x SR41 for days to flowering, SA1 x SR14 for plant height, SA2 x SR14 for head diameter, SA2 x SR13 followed by SA3 x SR13 for number of seeds per head, and SA3 x SR7 for one thousand seed weight. With regard to seed yield, the best hybrids with positive average heterosis were SA3 x SR41 (53.42%), SA4 x SR45 (52.75%), SA4 x SR1 (52.25%) and SA3 x SR10 (40.63%) which also combined with high seed yield of 1581 kg/ha, 1479 kg/ha, 1474 kg/ha, and 1457 kg/ha, respectively. These hybrids (involving the female line SA3 or SA4 and the male lines (SR10, SR13, SR41 and SR45) can be used in our breeding program in an attempt to develop local sunflower hybrid (s) with high seed yield and other important agronomic traits and for testing their yield potential and stability across locations and seasons.  أجريت هذه الدراسة بهدف تقدير التباين الوراثي و قوة الهجن  للإنتاجية ومكوناتها لأربعين هجين مفرد من محصول زهرة الشمس، نتجت من تهجين أربعة أمهات ذات عقم ذكرى سايتوبلازمى مع عشرة آباء معيدة للخصوبة. أجريت التجربة بمحطة بحوث سنار فى وسط السودان بالقطاع المروي لموسين             (صيف وشتاء2007). أستخدم تصميم القطاعات العشوائية الكاملة بثلاثة مكررات. كانت الصفات المدروسة هى عدد الايام حتى 50% إزهار، طول النبات، قطر القرص، عدد البذور بالقرص، وزن الآلف حبة، وانتاج البذور. أظهرت النتائج فروقات معنوية لكل الصفات في الموسمين مع تفوق الهجن وتباينها وراثياً مقارنة بالآباء. وفي التحليل المشترك لحساب قوة الهجين لكل الصفات كنسبة زيادة أو نقصان من متوسط الأبويين، ظهر أنّ الهــجينينSA2 x SR41  وSA3 x SR 41 هما الأفضل للإزهار والنضج المبكر، الهجين SA1 x SR14 لطول النبات، الهـجين SA2 x SR14 لقطر القرص ، الهجينين SA2 x SR13  و SA3 x SR13 لعدد البذور بالقرص، الهجين SA3 x SR7 لوزن الألف بذرة. أما بخصوص إنتاجية البذور أظهرت بعض الهجن نسبة قوة هجين موجبة SA3 x SR41 ) (53.42%، (52.73% ) SA4 x SR45،   SA4 x SR1   (52.25%)و SA3 x SR10 ((40.63% وإنتاجية بذور تقدر بـ 1581 كيلوجرام للهكتار، 1479 كيلوجرام للهكتار، 1474 كيلوجرام للهكتار و1459 كيلوجرام للهكتار علي التوالي. ويستنتج من هذه الدراسة ان الهجن التي يدخل في تركبيها الأم SA3 أو الأم SA4 مع الآباء SR41 ، SR45، SR13      و SR10 هى هجن متفوقة لإنتاجية البذور والصفات الأخرى ، ويمكن استخدام تلك الأمهات والآباء في تطوير هجن محلية مفردة من محصول الزهرة واختبار ثبات إنتاجيتها عبر المواسم والمواقع المختلفة.